Prevalence of Babesia and Ehrlichia in the Canine Population of North Gujarat Region - Prajapati, Ankit S; Patel, Kashyap A; Suthar, Abhinav N; Chauhan, Prakash M; Das, Bhupamani; Patel, Ramesh M (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was executed to know the prevalence of Babesia and Ehrlichia infection in canines of the northern region of Gujarat, India. A total of 6936 dogs presented at the Veterinary Clinical Complex, Sardarkrushinagar and Deesa from 2017 to 2021 were screened using the microscopic method for hemoprotozoal diseases, viz., Babesia and Ehrlichia. The age, sex, and breed-wise prevalence were estimated for both the diseases. The overall 3.29% (228/6936) prevalence of hemoprotozoal diseases was observed during the study period. A higher prevalence of Babesia (2.65%; 184/6936) was observed compared to Ehrlichia (0.63%; 44/6936). No significant difference was observed between sex with respect to the prevalence of these hemoprotozoan infections. The prevalence of hemoprotozoan infections was significantly higher in dogs aged 1-5 years, followed by less than one year. Among all breeds, the prevalence of Babesia was significantly higher in German shepherd followed by non-descript breed and Labrador retriever dogs; whereas, Ehrlichia was significantly higher in Labrador retrievers followed by non-descript dogs.